Percutaneous Ethanol Sclerotherapy of Symptomatic Nodules Is Effective and Safe in Pregnant Women: A Study of 13 Patients with an Average Follow-Up of 6.8 Years - Tamas Solymosi; Zsolt Melczer; Istvan Szabolcs; Endre V. Nagy; Miklos Goth (International Journal of Endocrinology)
Background. Because of the increased risk of surgery, thyroid nodules causing compression signs and/or hyperthyroidism are concerning during pregnancy. Patients and Methods. Six patients with nontoxic cystic, four with nontoxic solid, and three with overt hyperthyroidism caused by toxic nodules were treated with percutaneous ethanol injection therapy (PEI). An average of 0.68 mL ethanol per 1 mL nodule volume was administered. Mean number of PEI treatments for patients was 2.9. Success was defined as the shrinkage of the nodule by more than 50% of the pretreatment volume (V0) and the normalization of TSH and FT4 levels. The average V0 was 15.3 mL. Short-term success was measured prior to labor, whereas long-term success was determined during the final follow-up (an average of 6.8 years). Results. The pressure symptoms decreased in all but one patient after PEI and did not worsen until delivery. The PEI was successful in 11 (85%) and 7 (54%) patients at short-term and long-term follow-up, respectively. Three patients underwent repeat PEI which was successful in 2 patients. Conclusions. PEI is a safe tool and seems to have good short-term results in treating selected symptomatic pregnant patients. Long-term success may require repeat PEI.